PERAN LAYANAN DAYCARE BOCAH EMAS DI KAMPUS FKIP UNIVERSITAS SULTAN AGENG TIRTAYASA - Jamilatus Surifah; Fadlullah Fadlullah; Kristiana Maryani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
This study aims to describe the implementation of educational programs in early childhood in Golden Boy daycare and the implementation of care programs for early childhood. Data collection using the method of observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The validity of the data uses source triangulation techniques. The results of this study indicate that (1) The Golden Boy daycare day care system is full day and half day. The age of foster children in the Golden Boy daycare is 1 to 6 years old. The education program in the Golden Boy daycare uses stimulation education. By designing activities once a year with a working agenda and in a week making RPPM and RPPH. (2) Caregiving at the Golden Boy daycare applies life skills. The care process that is in the Golden Boy daycare is where children are taught independently from an early age where children can do their own daily activities which, of course, with the guidance of caregivers.